The Semantic Characteristic of the Concepts "Good and Evil" in German and Uzbek Languages - Nargiz Nazarova (Zien Journals, 2022)
This article covers the interpretation of the concepts "good" and "evil" in German and Uzbek on the basis of the opinions of scientists. The semantic features of this concept are explained with examples in both languages
Keywords: cognitive knowledge; cognitive orientation; semantic-derivation; phraseologism